2022
DOI: 10.1038/s41419-022-05409-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting glutamine metabolism in hepatic stellate cells alleviates liver fibrosis

Abstract: Glutamine metabolism plays an essential role in cell growth, and glutamate dehydrogenase (GDH) is a key enzyme. GDH promotes the metabolism of glutamate and glutamine to generate ATP, which is profoundly increased in multiple human cancers. Through in vitro and in vivo experiments, we verified that the small-molecule GDH inhibitor EGCG slowed the progression of fibrosis by inhibiting GDH enzyme activity and glutamine metabolism. SIRT4 is a mitochondrial enzyme with NAD that promotes ADP ribosylation and downre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…We used epigallocatechin-3-gallate (EGCG), an inhibitor of GDH 47 , to reverse Sirt4 knockout effects, i.e., preserving and directing glutamate to GABA. Oral gavage of EGCG (100 mg/kg) and BHB (500 mg/kg) for 4 weeks 48 , which had no impact on body weight (Supplementary Fig. S10a ) and food intake (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We used epigallocatechin-3-gallate (EGCG), an inhibitor of GDH 47 , to reverse Sirt4 knockout effects, i.e., preserving and directing glutamate to GABA. Oral gavage of EGCG (100 mg/kg) and BHB (500 mg/kg) for 4 weeks 48 , which had no impact on body weight (Supplementary Fig. S10a ) and food intake (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, HSC senescence was significantly induced by emodin at 20 μM consistent with the observation that emodin at 20 μM stimulated senescence in breast cancer cells (Zu et al, 2018), indicating that induction of senescence could be a common pharmacological action of emodin. We explored the reasons for emodin-induction of HSC senescence focusing on glutaminolysis, because glutaminolytic activity can fuel anapleurosis to satisfy the high bioenergetic and biosynthetic demands for maintaining the myofibroblastic phenotype (Yin et al, 2022). A recent study demonstrated that GLS1 was accumulated in hepatic fibrotic septa and inhibition of GLS1 reduced the fibrogenic activity of HSCs in nonalcoholic steatohepatitis patients (Du et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We explored the reasons for emodin‐induction of HSC senescence focusing on glutaminolysis, because glutaminolytic activity can fuel anapleurosis to satisfy the high bioenergetic and biosynthetic demands for maintaining the myofibroblastic phenotype (Yin et al, 2022). A recent study demonstrated that GLS1 was accumulated in hepatic fibrotic septa and inhibition of GLS1 reduced the fibrogenic activity of HSCs in nonalcoholic steatohepatitis patients (Du et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamine metabolism plays a crucial role in cell growth, and glutamate dehydrogenase (GDH) is a critical enzyme that promotes the metabolism of glutamate and glutamine to produce adenosine triphosphate (ATP). Sirt4 promotes adenosine diphosphate (ADP) ribosylation and downregulates GDH activity, inhibiting the conversion of glutamate to α-ketoglutarate during the tricarboxylic acid cycle [ 96 ]. In addition, Sirt4 deficiency leads to decreased expression and function of the glutamate transporter [ 97 ], which may be more important than Sirt4 deacetylation.…”
Section: The Origin and Function Of The Sirtuin Familymentioning
confidence: 99%